Fourier Transformation-Based Analysis of X-Ray Diffraction Pattern of Keratin for Cancer Detection - Alexander Alekseev; Oleksii Avdieiev; Sasha Murokh; Delvin Yuk; Alexander Lazarev; Daizie Labelle; Lev Mourokh; Pavel Lazarev (Crystals, 2025)
With the growing number of cancer cases and deaths around the world, fast, non-invasive, and inexpensive screening is paramount. We examine the feasibility of such cancer detection using the X-ray scattering properties of nails in the canine model. A total of 945 samples taken from 266 dogs were measured, with 84 animals diagnosed with cancer. To analyze the obtained X-ray diffraction patterns of keratin, we propose a method based on the two-dimensional Fourier transformation of the images. We compare 745 combinations of data preprocessing steps and machine learning classifiers and determine the corresponding performance metrics. Excellent classification results are demonstrated, with sensitivity or specificity achieving 100% and the best value for balanced accuracy being 87.5%. We believe that our approach can be extended to human samples to develop a non-invasive, convenient, and cheap method for early cancer detection.